Strengthening and Developing New Generation Heirs of Agriculturists According to the New Agricultural Theory, Mae Fah Luang District, Chiang Rai Province - สมณาศักดิ์ วราดวง; Imiwat, Prayoon (CRRU Law, Political Science and Social Science Journal, 2021)
The purposes of the research entitled “Strengthening and Developing New Generation Heirs of agriculturists according to the New Agricultural Theory, Mae Fah Luang District, Chiang Rai Province were : (1) to study methods of strengthening and developing new heirs of agriculturists according to the new agricultural theory and (2) to support and develop the new generation heirs of agriculturists to have knowledge and understanding and caused self-learning according to the New Agricultural Theory. The scope of the research consisted of heirs of Agriculturists who were students of the Office of Non-formal and Informal Education, Mae Fah Luang District, Chiang Rai Province, totaling 200 students, community leaders 8 people, agriculturists with 10 heirs (grandchildren) and 10 young generation heirs of agriculturists, totaling 228 people using the research tools; an in-depth interview, a focus group and a workshop. The results showed the strengthening and developing method of agriculturists according to the new agricultural theory It can be summarized in 3 ways: (1) The government helps the new generation heirs of agriculturists, such as training to provide knowledge from upstream to downstream. Access to land and capital (2) Promotion of association and building a network of the new generation heirs of agriculturists and (3) study visits on modern agricultural technology and learning from farmers who are successful in farming. Regarding to the support and development of the new generation heirs of agriculturists to have knowledge and understanding and caused self-learning according to the New Agricultural Theory, the researchers organized the workshop training for the students of the Office of Non-formal and Informal Education, Mae Fah Luang District, Chiang Rai Province, totaling 200 students.